2003
DOI: 10.1111/1540-6261.00539
|View full text |Cite
|
Sign up to set email alerts
|

The Value Spread

Abstract: We decompose the cross-sectional variance of ¢rms' book-to-market ratios using both a long U.S. panel and a shorter international panel. In contrast to typical aggregate time-series results, transitory cross-sectional variation in expected 15-year stock returns causes only a relatively small fraction (20 to 25 percent) of the total cross-sectional variance. The remaining dispersion can be explained by expected 15 -year pro¢tability and persistence of valuation levels. Furthermore, this fraction appears stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(96 citation statements)
references
References 25 publications
10
83
0
Order By: Relevance
“…29 The reader is referred to Campbell (1991) and Campbell and Shiller (1988a) for further details. 30 One can also use long horizon regressions instead of a VAR as in Cohen, Polk, and Vuolteenaho (2003) to decompose the returns. They argue that long horizon regression is a more appropriate approach for managed portfolios and estimating a VAR for the size-or BM-sorted portfolios might be problematic.…”
Section: The Return Decomposition Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The reader is referred to Campbell (1991) and Campbell and Shiller (1988a) for further details. 30 One can also use long horizon regressions instead of a VAR as in Cohen, Polk, and Vuolteenaho (2003) to decompose the returns. They argue that long horizon regression is a more appropriate approach for managed portfolios and estimating a VAR for the size-or BM-sorted portfolios might be problematic.…”
Section: The Return Decomposition Approachmentioning
confidence: 99%
“…For example, the VAR approach might incorrectly link the dependent variables for small firms to independent variables for large firms. This is especially problematic when one uses annual data to estimate the VAR as in Cohen, Polk, and Vuolteenaho (2003). However, the violation of this assumption is less of a problem for monthly data.…”
Section: The Return Decomposition Approachmentioning
confidence: 99%
“…Because we used the FamaFrench (1993) definitions, these portfolios' returns are essentially identical to those reported on Kenneth R. French's website. 6 Previous research (see, e.g., Asness, Friedman, Krail, and Liew 2000;Cohen, Polk, and Vuolteenaho 2003;Zhang 2005) has demonstrated that the "value spread" (the relative valuations of growth and value stock portfolios) can be used to forecast the value premium. Thus, in our robustness tests, we included the value spread as an explanatory variable.…”
Section: Datamentioning
confidence: 99%
“…10 Several studies (e.g., Asness, Friedman, Krail, and Liew 2000;Cohen, Polk, and Vuolteenaho 2003;Zhang 2005) have reported that the relative valuations of growth and value portfolios (the "value spread") can predict the value premium. That is, when growth stock valuations are much higher than value stock valuations, the subsequent value premium is large.…”
Section: Notesmentioning
confidence: 99%
“…Traditionally, forecasting regressions have been evaluated in time-series frameworks. However, with the increased availability of data, in particular international …nancial and macroeconomic data, it becomes natural to extend the single time-series framework to a panel data setting; for instance, Cohen et al (2003) and Polk et al (2006) rely on predictive panel data regressions in some of their analyses.…”
Section: Introductionmentioning
confidence: 99%